2016
DOI: 10.1136/bcr-2016-215909
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella spondylodiscitis of the thoracic vertebrae mimicking spine tuberculosis

Abstract: Extraintestinal Salmonella infection involving the thoracic spine is very rare. It commonly presents with non-specific chronic back pain and can occur with no gastrointestinal manifestation. Blood test results and imaging findings are often indistinguishable from more common chronic spine infections such as spine tuberculosis. Culture studies remain the key to establishing a definitive diagnosis and subsequently successful treatment. We report a case in which a patient presented with symptoms and signs suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Initially, we reviewed all cases of Salmonella-associated spondylitis reported in English with full texts available on PubMed and the Central Journal of Medicine, limited to adults 19 years and above. This search yielded 30 cases [ 5 - 34 ], 21 of which were identified as nontyphoidal Salmonella [ 5 - 25 ]. Of these, 17/21 (81.0%) patients reported local pain, and only 4/21 (19.0%) had no local pain (one case presented with impaired consciousness, one with spinal cord/peripheral nerve palsy, one with no clear identified cause, and one had no description provided).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, we reviewed all cases of Salmonella-associated spondylitis reported in English with full texts available on PubMed and the Central Journal of Medicine, limited to adults 19 years and above. This search yielded 30 cases [ 5 - 34 ], 21 of which were identified as nontyphoidal Salmonella [ 5 - 25 ]. Of these, 17/21 (81.0%) patients reported local pain, and only 4/21 (19.0%) had no local pain (one case presented with impaired consciousness, one with spinal cord/peripheral nerve palsy, one with no clear identified cause, and one had no description provided).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella and Mycobacterium infections occur in endemic regions. Both infections are characterized by the invasion of the bony spine, paravertebral tissue, spondylodiscitis, and psoas muscle abscesses (14,15). When investigating the potential source of infection, we discovered that the patient resided in an environment where cattle farming was commonplace; he consumed homemade air-dried raw beef and unpasteurized milk.…”
Section: Discussionmentioning
confidence: 99%
“…Pyogenic spondylodiscitis caused by Salmonella species is rare, as the organism usually manifests infection in the intestinal tract. There were two reported cases of Salmonella spondylodiscitis in Malaysia, and both were successfully treated with a course of antibiotics [1,2]. Mazlan et al reported that their patient was successfully treated with intravenous ampicillin 2 g for two weeks, followed by oral ciprofloxacin 750 mg for three months [1].…”
Section: Introductionmentioning
confidence: 99%
“…There were two reported cases of Salmonella spondylodiscitis in Malaysia, and both were successfully treated with a course of antibiotics [1,2]. Mazlan et al reported that their patient was successfully treated with intravenous ampicillin 2 g for two weeks, followed by oral ciprofloxacin 750 mg for three months [1]. Another case reported the use of ceftriaxone for two months in the treatment of Salmonella spondylodiscitis patient [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation